Hemostasis with prosthetic mesh in severe kidney trauma - Fernández Naone, Gonzalo; Keuchkerián, Marcel; Camejo, Marysol; Ferreiro, Gustavo; Pose, Juan; Kierszembaun, Carlos; Sciolla, Mariella (Cirugía del Uruguay, 1995)
A comparative study was carried out in 30 dogs between splenorraphy by means of two types of synthetic adhesives with and without free peritoneoplastic patch an ischemiant suture of the parenchyma with and without epiploplasty. The speed of the procedure, hemostasis efficiency and advantages and disadvantages of the tested procedures are the main points analysed by /he paper.